AVALIAÇÃO DO EFEITO COMPORTAMENTAL E NEUROPROTETOR DO ÔMEGA-3 ADMINISTRADO DURANTE O PERÍODO PRÉ-NATAL EM UM MODELO ANIMAL DA DOENÇA DE PARKINSON. - Pochapski, José Augusto (2016)
Parkinson's disease (PD) is the second most common neurodegenerative disease in the world population. However, its current treatment comes down to symptomatic relief. The omega-3 (-3) being an essential fatty acid for brain development, has been showing beneficial effects in PD. Therefore, the aim of this study was to evaluate whether treatment with -3 during early neurodevelopment periods provides a nootropic, antidepressant and/or neuroprotective effect in an animal model of PD. For this, female rats were treated with -3 during pregnancy (150, 300, 600 mg/Kg/day) and during pregnancy + lactation (300 mg/Kg /day). After completing two months of age the male offspring were submitted to the tests of sucrose preference, social recognition, object recognition and open field. Completing three months of age, the animals received in the prosencefalic unilateral 6-OHDA infusion and subsequent test of the rotational behavior or bilateral 6-OHDA infusion and subsequent tests of sucrose preference, social recognition and open field. A nootropic effect of -3 was observed from the results obtained on the tests of social recognition (-3 600) and object recognition (all groups -3). Regarding the animal model of PD, the -3 (all -3 groups) showed a reduction of the cognitive deficits induced by 6-OHDA, but without na antidepressive effect, although there was no demonstration of neuroprotection after unilateral lesion with 6-OHDA. Thus, this study the -3 demonstrated an nootropic and a possible neuroprotective effect of the -3 administration during the pregnancy period.